1998
DOI: 10.1002/(sici)1097-4628(19981017)70:3<599::aid-app22>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between conjugated polymer and fullerenes

Abstract: ABSTRACT:The fluorescence of Poly(2-methoxy,5-(2Ј-ethylhexloxy)-p-phenylene-vinylene) (MEH-PPV) quenched by fullerenes was examined, and the results indicate that this quenching is not dynamic. Strong interaction in the excited state between them may be caused by the photoinduced charge transfer and -conjugated system interaction. More direct and convincing evidence of the charge transfer complex are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 8 publications
(8 reference statements)
2
11
0
Order By: Relevance
“…4. The dependence on quencher concentration is linear with K SV Ϸ 2 ϫ 10 3 M Ϫ1 , which is consistent with the result reported by Zheng et al 12 From eqs. 2 and 3, it is clear that the PL quenching data alone cannot distinguish between dynamic or static processes.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…4. The dependence on quencher concentration is linear with K SV Ϸ 2 ϫ 10 3 M Ϫ1 , which is consistent with the result reported by Zheng et al 12 From eqs. 2 and 3, it is clear that the PL quenching data alone cannot distinguish between dynamic or static processes.…”
Section: Resultssupporting
confidence: 92%
“…The fluorescence set-up was arranged in such a way that the "filter effect" due to the absorption of PCBM was Ͻ6% even at the highest PCBM concentration. Nevertheless, to account for the small absorption of PCBM at the excitation and emission wavelength of MEH-PPV, the following equation was used to correct the fluorescence intensity 12 :…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Job plot and fluorescence titration experiments showed that a 1:1 complex was formed between 4 b and C 60 . Accordingly, the association constant K a of the complex 4 b·C 60 was calculated from a plot of F 0 /F cal (F cal : the calibrated fluorescence intensity [16] ) versus C 60 concentration to be 68 970 AE 1706 m À1 . Under the same conditions, it was found that addition of C 70 also led to a significant quenching of the fluorescence of 4 b.…”
Section: Structures Of the Triptycene-derived Calix[6]arenes In Solutmentioning
confidence: 99%
“…Where E and E are the oxidation and reduction potentials relative to Ag/Ag+ electrode [40]. The onset of QUI-OCZ oxidation is +1.34 V and reduction is −1.23 V vs. Ag/Ag + electrode, which is corresponding to HOMO level of −5.74 eV and LUMO level of −3.17 eV respectively.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%